2013
DOI: 10.1097/ede.0b013e3182944410
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet, Cognitive Function, and Dementia

Abstract: Published studies suggest that greater adherence to Mediterranean diet is associated with slower cognitive decline and lower risk of developing Alzheimer disease. Further studies would be useful to clarify the association with mild cognitive impairment and vascular dementia. Long-term randomized controlled trials promoting a Mediterranean diet may help establish whether improved adherence helps to prevent or delay the onset of Alzheimer disease and dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
273
1
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 468 publications
(290 citation statements)
references
References 46 publications
7
273
1
9
Order By: Relevance
“…Among theoretically (a priori) defined patterns, the Mediterranean diet has been associated with positive health outcomes in many studies (10)(11)(12)(13)(14) . Similarly, a Nordic Food Index has been suggested for the Nordic countries.…”
mentioning
confidence: 99%
“…Among theoretically (a priori) defined patterns, the Mediterranean diet has been associated with positive health outcomes in many studies (10)(11)(12)(13)(14) . Similarly, a Nordic Food Index has been suggested for the Nordic countries.…”
mentioning
confidence: 99%
“…cluster analysis) have been linked to reduced risk of common age-related diseases (e.g. CVD, stoke and dementia) (46)(47)(48)(49) and mortality (50,51) . Compared with less healthy DP, healthy DP are characterised by higher intake of beneficial foods (e.g.…”
Section: Dietary Patterns and Health In The Very Oldmentioning
confidence: 99%
“…Since the first published studies showing the cognitive benefits of adherence to the Mediterranean Diet, studies from New York, rural Utah, and Australia have shown that greater compliance with such dietary patterns from the middle decades of life and beyond is associated with reduced risk for MCI and Alzheimer's disease and slower progression of the disease (89,90,93,97,(106)(107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117). Similarly, high adherence to DASH and other balanced dietary patterns that emphasize intake of fruits, vegetables, cereals, and whole grains have also been associated with a lower likelihood of developing Alzheimer's disease (90,97,110,115).…”
Section: Grain-based Foods As Part Of Healthy Dietary Patternsmentioning
confidence: 99%